Chữ "đạt" trong dịch thuật - Lê, Hoài Ân (H. : ĐHQGHN, 2017)
Translation is a very complex field. What a translator is and does, how a translator should translate, what constitutes a good translation, what we should do to develop better training grograms for translation professionals and to evaluate the quality of a translation? -this question is not easy to answer. This article analyzes the standard “attainment” in the translation. In my opinion, “attainment” in the translation is completeness in substance (informative completeness), exactness in substance, formative adequacy, exactness in terminology and adequacy with regard to knowledge of readers/translationrecipients. I hope that this paper is a small contribution for the translation teaching at College of Foreign Languages -VNU Hanoi.